Interactions between soil gravel content and neighboring vegetation control management in oak seedling establishment success in Mediterranean environments (Forest Ecology and Management, 2012)
Restoration of vegetation in Mediterranean areas is limited by several factors, some of which are poorly understood, such as soil stoniness and competition with natural vegetation. This paper analyzes the interaction between weed management treatments (cultivation, herbicide, mulch and tree shelter) and the proﬁle stoniness in Holm oak (Quercus ilex L. sub. ballota (Desf.) Samp.) seedling establishment in Mediterranean areas. Our experimental trials show that proﬁle gravel content is a key factor in seedling survival, in which optimal reforestation sites would be deﬁned by gravel content <5%; transitional sites by 5% 6 gravel content 6 15% and excluded sites by gravel content >15%. The soil proﬁle gravel content caused severe water limitations, especially important in the ﬁrst year after planting, which inﬂuenced the effectiveness of neighboring vegetation control techniques for seedling establishment success. This study also conﬁrms the positive effect of competition management techniques on survival. The treatments tested showed an improvement in the survival rate, but not in growth rate, over the control treatment throughout the monitoring period. We have obtained a vegetation response model in which the beneﬁcial effects of competition control on the success of oak seedling establishment are distorted by soil gravel content.